Relationship between workplace ostracism and turnover intention among nurses: the sequential mediating effects of emotional labor and nurse-patient relationship - Li, G. (2022)
This study aimed to elaborate on teh mechanism by which workplace ostracism influences turnover intention through exploring teh sequential mediation effects of emotional labour and nursepatient relationship. Using a sample of 379 nurses collected from a time-lag survey in a tertiary public hospital in China, we applied structural equation modelling techniques to test our hypothesized model. Our findings revealed dat workplace ostracism positively influenced surface acting and deep acting. Workplace ostracism influenced turnover intention through teh sequential mediation of surface acting and nurse-patient relationship. Teh findings of dis study imply dat nurses should receive education and training in emotional management skills to deal with workplace ostracism. Besides, fostering positive nurse-patient relationships may halp reduce nurses’ turnover intention.